2002
DOI: 10.1093/jexbot/53.367.351
|View full text |Cite
|
Sign up to set email alerts
|

Linear amplification coupled with controlled extension as a means of probe amplification in a cDNA array and gene expression analysis during cold acclimation in alfalfa (Medicago sativa L.)

Abstract: This study describes a rapid and simple way to amplify limited amounts of probes used for cDNA array hybridization while maintaining the original representation of transcripts in the samples. The approach is based on linear amplification of cDNA-coupled controlled extension of amplified products and yielded a 50-75-fold increases in hybridization signal intensity. Controlled extension of products is achieved either by adjusting the amplification conditions or by using a digested template. Linear amplification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In order, to isolate cold‐induced genes showing significant difference in expression between the Rambler and Moapa 69 genotypes, we screened an alfalfa cDNA library prepared from cold‐stressed Rambler RNA, using a modified differential hybridization technique. This technique utilized the LACE ( l inear a mplification with c ontrolled e xtension) approach to enrich the cDNA population (used as a probe in hybridization) for 3′ ends (Ivashuta et al ., 2002). Such an approach to probe amplification may improve the hybridization kinetics of complex probes and reduce the possibility of cross‐hybridization of long transcripts that share significant sequence homology.…”
Section: Resultsmentioning
confidence: 99%
“…In order, to isolate cold‐induced genes showing significant difference in expression between the Rambler and Moapa 69 genotypes, we screened an alfalfa cDNA library prepared from cold‐stressed Rambler RNA, using a modified differential hybridization technique. This technique utilized the LACE ( l inear a mplification with c ontrolled e xtension) approach to enrich the cDNA population (used as a probe in hybridization) for 3′ ends (Ivashuta et al ., 2002). Such an approach to probe amplification may improve the hybridization kinetics of complex probes and reduce the possibility of cross‐hybridization of long transcripts that share significant sequence homology.…”
Section: Resultsmentioning
confidence: 99%
“…A, Alignment of predicted CAS15 polypeptides encoded by M. falcata l7H-15-2 (partial length), and M. truncatula lJ4-15-1 genomic clones with those encoded by the expressed sequences from alfalfa CAS15 (GenBank accession L12461; Monroy et al, 1993), and M. truncatula EST1224309 (GenBank accession DW015348). B, Alignment of CAS30 and CAS31 polypeptides encoded by M. falcata lV2-17 and M. truncatula lJ2-17-2 genomic clones with those encoded by alfalfa expressed sequence AF411554 (Ivashuta et al, 2002) and M. truncatula TC77327. The downward pointing arrow identifies Gln residues 69 and 89 in M. falcata and M. truncatula CAS30/31 polypeptides, respectively, whose codon is split between Exons 1 and 2.…”
Section: Cas Polypeptide Structurementioning
confidence: 99%
“…, score 1,349; Ivashuta et al, 2002), and the M. truncatula tentative consensus sequence TC100921 (E 5 7.4e 2208 , score 4,695). No single M. truncatula EST encompassed the entire predicted coding sequence (CDS; Fig.…”
mentioning
confidence: 99%
“…Protein spot differences between the gels were identified by visual examination and by computation of spot volume ( Figs 7B-D, 8A-C). The transition from NA to CA induced a large number of changes in the spot distribution on 2D gels, which was consistent with previous literature showing that CA results in major changes in transcription and induction of new proteins (Ndong et al, 2001;Fowler and Thomashow., 2002;Ivashuta et al, 2002;Seki et al, 2002;Fabio et al, 2003;Rabbani et al, 2003). Differences between CA and SZA treatments were much more subtle, with changes of new proteins or proteins lost among the minor proteins on the gel; other changes were in the increasing or decreasing abundance of proteins.…”
Section: Proteome Changesmentioning
confidence: 99%
“…With the advent of genomics tools, large-scale assays have been applied to the examination of transcription patterns of CA in several plants. Large-scale transcriptome studies with DNA arrays have shown that CA induces up-as well as downregulation of a very large number of mRNAs (Ndong et al, 2001;Fowler and Thomashow, 2002;Ivashuta et al, 2002;Seki et al, 2002;Fabio et al, 2003;Rabbani et al, 2003). These assays have shown that diverse plants respond in similar ways by inducing many of the same types of mRNAs such as COR (cold-regulated) proteins and dehydrins.…”
Section: Introductionmentioning
confidence: 99%